Improved Accuracy and Safety of Intracorporeal Transpedicular Bone Grafting - using Contrast Impregnated Bone: A Case Report - Chiu, CK (Malays Orthop J, 2014)
A method of transpedicular bone grafting using contrast impregnated bone to improve the visualization of bone graft on the image intensifier is reported. A - 36-year old man who had sustained traumatic burst fracture of T12 vertebra, with Load-Sharing Classification (LSC) score of 8, was treated with posterior short segment fusion from T11 to L1 with transpedicular bone graft of T12 vertebra. We were able to correct the kyphotic end plate angle (EPA) from 19º to 1.4º. Anterior bone graft augmentation was achieved with contrast enhaced transpedicular bone grafts. At six months follow up, CT scan showed good bony integration of the anterior column with EPA of 4.5º and two years later, radiographs showed EPA of 7.6 º.